Implementation of Character Education Through Culture 5S (Senyum, Sapa, Salam, Sopan dan Santun) At State Junior High School 2 Ngawi (Smpn 2 Ngawi) East Java Indonesia - Rahayu, Sri Wening (Faculty of Education Universitas Negeri Malang, 2019)
This study aims to describe and find the implementation of character education through the 5S culture at SMPN 2 Ngawi. Data collection techniques in this study using in-depth interviews, participatory observation and documentation. The results show that the implementation of character education through the application of 5S culture in schools has proven effective, which can result in the cultivation of livable values of life, which can be a provision of community life. If the application of the 5S culture is consistent, it can automatically improve school performance but also the school into a character education center followed by other schools.Keywords: Character Education, Culture 5, SMPN 2 Ngawi